2020
DOI: 10.24016/2020.v6n1.225
|View full text |Cite
|
Sign up to set email alerts
|

Validez e invarianza según sexo y edad de la Escala Paykel de Ideación Suicida en adolescentes peruanos

Abstract: Jonatan Baños-Chaparro y Cris an Ramos-Vera CITARLO COMO: Validez e invarianza según sexo y edad de la Escala Paykel de Ideación Suicida en adolescentes peruanos Validity and invariance according to sex and age of the Paykel Scale of Suicide Idea on in Peruvian adolescents

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 25 publications
(36 reference statements)
0
5
0
3
Order By: Relevance
“…El uso de los modelos MIMIC es muy apropiado en este estudio, los cuales se han utilizado en estudios peruanos recientes (Baños & Ramos, 2020;Bollen & Bauldry, 2011;Ramos & Sáenz, 2021).…”
Section: Análisis De Datosunclassified
“…El uso de los modelos MIMIC es muy apropiado en este estudio, los cuales se han utilizado en estudios peruanos recientes (Baños & Ramos, 2020;Bollen & Bauldry, 2011;Ramos & Sáenz, 2021).…”
Section: Análisis De Datosunclassified
“…Por ejemplo, en la parte teórica se informa sobre los diversos instrumentos psicométricos de evaluación para las conductas suicidas, y en la parte práctica, la capacitación específica en la calificación e interpretación de los instrumentos de evaluación. Informar la utilidad de cada instrumento, por ejemplo: diseñado para población infantil, adolescente, adulto o condición clínica (Baños-Chaparro et al, 2021e;Baños-Chaparro & Ramos-Vera, 2020). Asimismo, señalar la importancia de los instrumentos de cribado y extensos, aplicabilidad en entornos clínicos, escolares y población general, el objetivo de evaluación (ideación suicida pasiva o activa, autolesiones, planificación o intento de suicidio), entre otros aspectos más.…”
Section: Figuraunclassified
“…Suicidal ideation (SI) encompasses a range of thoughts, wishes, and concerns related to death and suicide being a widespread phenomenon in the general population. It can manifest itself actively, with concrete thoughts of selfelimination, or passively, expressing a desire to die or disappear (Baños-Chaparro et al, 2020). The prevalence of SI in a meta-analysis and systematic review in the general European population showed a higher lifetime prevalence of wishes to die (20 %) and suicidal ideation (9 %) compared to suicide planning (2 %) and suicide attempts (3 %).…”
Section: Introductionmentioning
confidence: 99%
“…In the Peruvian context, a study conducted on adolescents during the pandemic revealed that 21% expressed having had suicidal thoughts (Baños-Chaparro et al, 2020). Furthermore, in the last three years, the frequency of completed suicides in Peru has increased, with an average of 2 suicides per day each year (Baños-Chaparro et al, 2021).…”
Section: Introductionmentioning
confidence: 99%